How Good Corporate Governance Influences Company Value through Financial Performance - Muslim, Muslim (Advances in Applied Accounting Research, 2023)
Purpose: This study examines the impact of Good Corporate Governance (GCG) on firm value, with Return on Investment (ROI) as an intervening variable. It aims to clarify whether GCG directly influences firm value or if financial performance mediates this relationship, addressing inconsistencies in prior studies. Research Design and Methodology: The research employs an associative quantitative approach, analyzing 31 LQ 45 companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2019. A purposive sampling method was employed to select companies that met specific financial reporting criteria. Secondary data was obtained from official financial reports, and analysis was conducted using classical assumption tests, multiple regression, the Sobel test, and hypothesis testing via SPSS 21. Findings and Discussion: The results indicate that GCG has a positive and significant impact on financial performance and firm value. Additionally, financial performance serves as a mediating variable, reinforcing agency theory, which suggests that governance mechanisms reduce conflicts between managers and shareholders, ultimately enhancing firm value. Implications: This study contributes to corporate governance literature by demonstrating the role of financial performance in mediating the GCG-firm value relationship. Practically, companies should strengthen governance practices to improve economic performance and attract investors. Future research should investigate additional factors, such as macroeconomic conditions, to further explain variations in firm value.